2013
DOI: 10.1152/ajpregu.00089.2013
|View full text |Cite
|
Sign up to set email alerts
|

Repeated variate stress in male rats induces increased voiding frequency, somatic sensitivity, and urinary bladder nerve growth factor expression

Abstract: Merrill L, Malley S, Vizzard MA. Repeated variate stress in male rats induces increased voiding frequency, somatic sensitivity, and urinary bladder nerve growth factor expression. Am J Physiol Regul Integr Comp Physiol 305: R147-R156, 2013. First published May 8, 2013 doi:10.1152/ajpregu.00089.2013.-Stress exacerbates symptoms of functional lower urinary tract disorders including interstitial cystitis (IC)/bladder pain syndrome (BPS) and overactive bladder (OAB) in humans, but mechanisms contributing to symp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
79
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 46 publications
(87 citation statements)
references
References 79 publications
(133 reference statements)
6
79
0
2
Order By: Relevance
“…The present studies confirmed our recent description (37) that RVS in male rats produces urinary bladder dysfunction characterized by decreased bladder capacity and void volume and increased voiding frequency. Furthermore, these studies demonstrated several novel findings with respect to TRPV4 channel expression in the urinary bladder and the effects of pharmacological manipulation following RVS on urinary bladder function.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…The present studies confirmed our recent description (37) that RVS in male rats produces urinary bladder dysfunction characterized by decreased bladder capacity and void volume and increased voiding frequency. Furthermore, these studies demonstrated several novel findings with respect to TRPV4 channel expression in the urinary bladder and the effects of pharmacological manipulation following RVS on urinary bladder function.…”
Section: Discussionsupporting
confidence: 92%
“…We also demonstrated that RVS produces bladder dysfunction in rats characterized by decreased bladder capacity, intercontraction interval, and void volume (37). These results were confirmed in the present experiments (Table 1).…”
Section: Effects Of Trpv4 Agonist and Antagonist On Bladder Functionsupporting
confidence: 91%
See 3 more Smart Citations